Role of Satkriyakala in Early Detection and Prevention of Lifestyle Disorders in Ayurveda - Dr. Shyam K. Umaretiya,; Dr. Yogita B. Mandle,; Prof. (Dr.) Sreekanth V. M., (The Bioscan, 2026)
Satkriyakala is one of the essential Ayurvedic concepts that explains the six stages of disease development in sequence, which provides a distinctive model of early diagnosis and preventive medicine. In contemporary world, lifestyle diseases like diabetes, obesity and cardiovascular diseases are on the rise at a high rate because of the sedentary lifestyle and unhealthy eating habits. The proposed study will focus on examining how Satkriyakala can be utilized in the early identification and prevention of the disorders with a description and analytical review of classical Ayurvedic texts and modern literature. They have the stages that include Sanchaya, Prakopa, Prasara, Sthanasamshraya, Vyakti, and Bheda, which are the opportunities to intervene on time before the manifestation of irreversible pathology. Detection of the initial symptoms like Dosha accumulation and Purvarupa can help clinicians to put preventative measures in place like diet, lifestyle changes and treatment. Hence, Satkriyakala is a predictive and preventive measure, which is a hybrid of Ayurvedic traditional wisdom and modern disease management and holistic health promotion.